PENERAPAN MODEL PROBLEM BASED LEARNING (PBL) UNTUK MENINGKATKAN PEMBELAJARAN IPA SISWA KELAS V SDN PRINGAPUS 2 KECAMATAN DONGKO KABUPATEN TRENGGALEK - Rachmawati, Linda (Universitas Nusantara PGRI Kediri, 2015)
Abstract: Found the problem that science teaching in class V SDN Pringapus 2 Trenggalek still centered on the teacher, this adversely affects the activity and student learning outcomes in science subjects. The research was conducted with the aim to describe the application of the model PBL, student activity when applied to the model PBL, and student learning outcomes after application of PBL models. This study design was used classroom action research conducted by two cycles, with the subject of fifth grade students of SDN Pringapus 2 Trenggalek. The results showed that the application of the model PBL can improve pembelajran IPA, basic competence